Elasticity of intertemporal substitution in the euro area - Michal Marenčák; Giang Hong Nghiem (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2024)
This paper estimates the elasticity of intertemporal substitution for the euro area. It leverages the unique design of the Consumer Expectations Survey in Europe to directly infer it from the Euler equation. Our final estimates range between 0.7 and 0.8 for the euro area as a whole, which are higher than those for the US. We also observe economically sizeable heterogeneity across the member states, and over time. Belgium, Germany, and the Netherlands have lower elasticity compared to France, Spain, and Italy. The implications are discussed.
Keywords: D12; D15; D84; E21; 330; inflation; expectations; consumption; intertemporal elasticity of substitution; Euler equation; Consumer Expectations Survey